Methodological Aspects of the Delimitation of Peripheral Areas: Approaches of Russian Scholars - DVORYADKINA, Elena B.; KAIBICHEVA, Catherine I.; BAUSOVA, Julia S. (Journal of Environmental Management and Tourism; Vol 8 No 3 (2017): JEMT Volume VIII Issue 3(19) Summer 2017DO - 10.14505//jemt.v8.3(19).18, 2017)
The paper deals with the methodological approaches to delimiting peripheral areas at regional level (the RF subjects) adopted in the Russian scientific literature and practice. The authors developed and tested their own methodology for delimiting a region’s peripheral areas, which involves using algorithms for assessing transport accessibility of territories, the level of their socio-economic development and economic potential. The main advantages of the proposed methodology are attention to the current municipal structure of Russian regions, the use of statistical data open to general public and description of periphery from the standpoint of managerial (political), geographical and economic approaches. The authors determined the major directions and problems of further improvement of methodological approaches to the definition of periphery at regional level (the RF subject).